Methane seepage at Vestnesa Ridge (NW Svalbard) since the Last Glacial Maximum. (1st August 2018) - Schneider, A.; Panieri, G.; Lepland, A.; Consolaro, C.; Crémière, A.; Forwick, M.; Johnson, J.E.; Plaza-Faverola, A.; Sauer, S.; Knies, J.
Abstract: Multiple proxies in the geological record offshore NW Svalbard track shallow subseafloor diagenesis and seafloor methane seepage during the Last Glacial Maximum (LGM) extent and the disintegration of the Svalbard Barents Sea Ice Sheet (SBIS). Vestnesa Ridge, located at 79°N and in 1200 m water depth, is one of the northernmost known active methane seep sites and is characterised by a subseafloor fluid flow system, numerous seafloor pockmarks and gas flares in the water column. In this study, we develop a Late Pleistocene and Holocene stratigraphic framework, use stable oxygen and carbon isotope signatures (δ 18 O, δ 13 C) of benthic and planktic foraminifera, the mineralogical and carbon isotope composition of methane-derived authigenic carbonate (MDAC) and sediment geochemical data of ten sediment cores to assess methane seepage variability on Vestnesa Ridge. The studied cores cover the age range between 31.9 and 10 cal ka BP and record 32 negative δ 13 C excursions in benthic and planktic foraminifera with amplitudes down to −29 ‰ VPDB. These δ 13 C excursions are often associated with elevated Ca/Ti and Sr/Ti elemental ratios in sediments and MDAC nodules. The precipitation of MDAC overgrowth on foraminiferal tests explains most of the negative δ 13 C excursions. In this dataset, the oldest recorded methane emission episodes on Vestnesa Ridge occurred between the LGM (24–23.5 cal ka BP) and Heinrich Event 1 (HE 1; 17.7–16.8 cal ka BP). Geological indicators for past subseafloor methane cycling and seafloor methane seepage, such as negative foraminiferal δ 13 C excursions, MDAC nodules, and elevated Sr/Ti elemental ratios recorded in post-LGM sediments, possibly represent vertical migration of the sulphate-methane transition zone (SMTZ) and post-date sedimentation by up to 13.4 ka. However, it is important to note that indications of post-LGM seafloor methane seepage at Vestnesa Ridge also correspond to the established methane efflux chronology for the adjacent Barents Sea shelf, implying that glacio-isostatic adjustments and associated re-activation of pre-existing deep-seated faults after disintegration of the SBIS are likely important controlling factors on fluid migration towards the seafloor. Highlights: Multiple proxies document diagenesis and methane seepage at Vestnesa Ridge since the LGM. Diagenetic alteration of foraminifera and MDAC precipitation may postdate the host sediment age by up to 13.4 ka. Timing of methane seepage corresponds to the LGM and deglaciation of the SBIS. Glacio-isostatic adjustments may be a key control on methane seepage.